Lesson Study in initial training: an interdisciplinary academic experience. A case study in Spain. - Mayorga-Fernández, María Josefa; Peña-Trapero, Noemí; De-la-Rosa-Moreno, María Lourdes (Emerald, 2021)
Purpose – This paper focuses on analysis of the incorporation of a Lesson Study cycle within the university training proposal, as a teaching strategy in initial training in the Infant Education Degree. Design/methodology/approach – Qualitative research was conducted through a case study methodology. Findings – Proposing training strategies based on this methodology encourages both the reconstruction of future teachers’ practical knowledge and also adequate professional development from initial training. Research limitations/implications – The main constraint in the study was the cost-benefit ratio, since this experience has required significant practical and emotional dedication by the people involved, while the expected results have only been partially evident in the students. This would seem to imply that the strategy requires continuity over time in order for future education professionals to take it fully on board. Practical implications – More continuity in such experiences would be required in order to fully analyse their actual value. To this end, the experiences need to be more closely related to the university curriculum, and there must be greater coordination between the subjects in order to ensure a holistic approach to LS. Originality/value – This article sets out an LS experience as a collaborative action-research strategy that promotes the reconstruction of students’ practical knowledge and their professional development in initial training
Keywords: Profesores - Formación profesional; Enseñanza - Innovaciones; Didáctica; Lesson Study; Higher education; Professional development; Training strategies; Initial training; Qualitative research